Prevalence of Posttraumatic Stress Disorder in Patients With Multiple Sclerosis. Issue 2 (February 2018) - Carletto, Sara; Borghi, Martina; Scavelli, Francesco; Francone, Diana; Perucchini, Maria Luisa; Cavallo, Marco; Pagnini, Francesco; Bertolotto, Antonio; Oliva, Francesco; Ostacoli, Luca
Abstract : Abstract: Chronic and life-threatening illnesses, such as multiple sclerosis (MS), have been identified as significant stressors potentially triggering posttraumatic stress disorder (PTSD). The study aims to investigate the prevalence of PTSD according to Diagnostic and Statistical Manual of Mental Disorders, 4th Edition, Text Revision ( DSM-IV-TR ) criteria in a large sample of patients with MS. A total of 988 patients with MS were screened with the Impact of Event Scale–Revised, and then assessed with the PTSD module of the Structured Clinical Interview for DSM-IV and with the Clinician-Administered PTSD Scale to confirm PTSD diagnosis. Posttraumatic symptoms were reported by 25.5% of the sample. A confirmed diagnosis of PTSD was found in 5.7% of patients, but prevalence could reach 8.5%, including also dropout patients. Further studies are needed to evaluate if adjustment disorder could better encompass the frequently encountered subthreshold posttraumatic stress symptoms and how clinicians can deal with these symptoms with appropriate interventions.